Government Sponsored Advertisements: Do They Cultivate Higher Order Thinking Skills? - Dhanapal, Dr Saroja; Sakthi Anantha, Sharmaine; Binti Omar Farouk, Riaz Fathima (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Advertising can be defined as an openly sponsored offering of goods, services, or ideas through any medium of public communication. Advertising, in the past decade has undergone significant development and it now comprises television, radio and internet besides the traditional print media. Levens (2012) defines advertising as the paid, non -personal communication of a marketing message by an identified sponsor through mass media which acts as a tool for a company to massively introduce a product or service to the consumers using the available media that are endless starting from billboards, posters, wall paintings to the most explicit places like the back of event tickets or even the public transport t hat roams all over the city. Government sponsored advertisements (GSA ) or public service advertisement (PSA) on the other hand can be defined as messages in the public interest disseminated by the media without charge. Today, public serviceadvertising has been increasingly used in a non-commercial fashion in several countries across the world in order to promote various social causes (Devadas and Manohar, 2011). The objective is to raise awareness, change public attitudes and behavior towards social issues. The purpose of this paper is to explore as to whether advertisement s sponsored by the Malaysian government merely disclose social responsibility information or do they go beyond this to inculcate Higher Order Thinking Skills among the audience from the three generations; Baby boomers, Generation X and Generation Y. As such, a purposive sampling was used in the selection of the advertisements for the study based on thecontent that catered for the three generations. To identify whether the advertisements inculcate Higher Order Thinking Skills (HOTS) according to Blooms Taxanomy (1990), the contents of the advertisements were analysed using a framework based on an integrated approach combining content and semiotic analysis. To further support the findings, a survey was carried out among 100 samples to identify their perception on government sponsored advertisements. The samples for the survey were also selected using a purposive sampling. This was to ensure that there were representatives from the three generations. It is hoped that this study will contribute to the scarce l iterature on the effectiveness of advertisements in cultivating Higher Order Thinking Skills.